BETWEEN JUSTICE AND COMPLEXITY: UNVEILING TAX MORALE IN PEKANBARU - Fionasari, Dwi; Suci, Rama; Putri, Annie; Iznillah, Muhammad Luthfi (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Taxation is a critical foundation for sustainable national growth, with tax morale serving as a key determinant of voluntary compliance. This study focuses on understanding tax morale by examining the effects of tax burden, system complexity, and tax justice. Primary data were collected from 100 Micro, Small, and Medium Enterprises (MSMEs) through an e-questionnaire using purposive sampling and analyzed with SEM-PLS. The findings reveal that perceived tax fairness exerts a positive and significant influence on tax morale, while system complexity has a significant negative effect. In contrast, tax burden shows no significant impact. These results highlight that fairness and simplicity in the tax system shape taxpayer attitudes more strongly than nominal tax levels. The study suggests that tax administrators should streamline procedures, ensure a fair distribution of tax burdens, and build a tax structure that is more transparent and just.